Sex Discrepancy Observed for Gestational Metabolic Syndrome Parameters and Polygenic Risk Associated With Preschoolers’ BMI Growth Trajectory: The Ma’anshan Birth Cohort Study - Zhu, Bei-bei; Gao, Hui; Geng, Meng-long; Wu, Xiulong; Tong, Juan; Deng, Fen; Zhang, Si-ying; Wu, Li-hong; Huang, Kun; Wu, Xiao-yan; Gan, Hong; Zhu, Peng; et al. (Frontiers in Endocrinology, 2022)
Background Few studies have investigated the associations of childhood growth trajectories with the prenatal metabolic risks of mothers and their interaction with children’s genetic susceptibility. Objective To investigate the effects of gestational metabolic syndrome (GMS) risks and children’s polygenic risk scores (PRSs), and their interaction effect on the BMI trajectory and obesity risk of offspring from birth to 6 years of age. Methods A total of 2,603 mother-child pairs were recruited from the Ma’anshan birth cohort (Anhui Province of China) study. Data on maternal prepregnancy obesity, gestational weight gain (GWG), gestational diabetes mellitus (GDM), and hypertensive disorders of pregnancy (HDP) were used to evaluate maternal GMS risk. In addition, 1,482 cord blood samples were used to genotype 11 candidate single-nucleotide polymorphisms (SNPs) to calculate children’s PRSs. The latent class growth model using the longitudinal BMI-for-age z scores (BMIz) was applied to validly capture the BMIz growth trajectory. Results Maternal GMS status was associated with higher BMIz scores and with an increased risk of overweight/obesity. Positive relationships were revealed between PRS and the risk of overweight/obesity among girls. Additionally, maternal GMS significantly interacted with the child’s PRS on BMIz scores and the risk of overweight/obesity among girls. Hierarchical BMI trajectory graphs by different exposure groups showed consistent findings, and both boys’ and girls’ BMIz trajectories were divided into three groups. Among girls, the higher the GMS risk or PRS they had, the higher the probability of being in the high BMIz trajectory group. Conclusions Maternal GMS status increased BMIz scores and the risk of obesity in both boys and girls and elevated the child’s BMI trajectory from birth to 6 years of age among girls. PRSs were significantly associated with children’s BMI trajectory and the risk of obesity and modified the associations between maternal GMS status and obesity biomarkers only among girls. Thus, regarding childhood obesity, steps should be taken to decrease maternal metabolic risks before and during pregnancy, and sex discrepancies should be noted to identify high-risk populations after birth to hierarchically manage them.